2023
DOI: 10.1017/jns.2023.3
|View full text |Cite
|
Sign up to set email alerts
|

Caecal digestibility as an approximation of ileal protein digestibility evaluation in rats

Abstract: The rat model can be used to assess ileal protein digestibility rapidly and in first intention, but no standardised method exists. Our objective was to compare methods to assess protein digestibility, depending on collection site (ileum/caecum) and use of a non-absorbable marker. A meal containing either casein, gluten or pea protein and chromium oxide as non-absorbable marker was given to male Wistar rats and the entire digestive content was collected 6 h later. Total chromium recovery was incomplete and vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…This method consists of collecting quantitatively the cecal digesta during a limited post-digestion period (usually 6 h), allowing a compromise between complete digestion of the test meal and minimal duration of fermentation. Comparable digestibility values have been obtained at the ileal and caecal levels in rats for different protein sources (21) . In the present study, high nitrogen and amino acid true orocaecal digestibilities were found for both T− and T+++ diets, with values above 90 %.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This method consists of collecting quantitatively the cecal digesta during a limited post-digestion period (usually 6 h), allowing a compromise between complete digestion of the test meal and minimal duration of fermentation. Comparable digestibility values have been obtained at the ileal and caecal levels in rats for different protein sources (21) . In the present study, high nitrogen and amino acid true orocaecal digestibilities were found for both T− and T+++ diets, with values above 90 %.…”
Section: Discussionmentioning
confidence: 99%
“…True orocaecal nitrogen and amino acid digestibilities were determined in rats euthanised 6 h after meal intake. The collection of digesta 6 h after meal ingestion facilitates a compromise between complete digestion and a minimal duration of caecal fermentation (21) . Orocaecal nitrogen digestibility was calculated as follows: where N ingested is the quantity of nitrogen ingested from the meal (in mmol), N caecum total is the total nitrogen content (in mmol) in the caecum of T+++ and T− rats, and N caecum endogenous is the endogenous loss of nitrogen in the caecum (in mmol).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation